Preface to a socio-critics of adaptation to cinema - Carcaud, Monique; Clerc, Jeanne Marie (Íkala, Revista de Lenguaje y Cultura, 1999)
Cinematographic adaptation of literary works is by itself an investigation field for cultural creation. Sociocriticism offers us the methodological tools to analyze the dynamics and variability of two semiotics processes: reading and writing both in their book or screen versions.